Immunotherapeutic Applications of NK Cells - Carter T. Davis; David Rizzieri (MDPI AG, 2015)
Natural Killer (NK) cells are lymphoid cells that exhibit an innate response against virus-infected cells. These cells are also capable of mounting an immune response against tumor cells after education through major histocompatibility complex (MHC) class I molecules. NK cell regulation is mediated through IFN-gamma and IL-15, important cytokines which can drive NK cell expansion in vivo. Previous studies have shown effective infusion of allogeneic NK cells after lymphodepleting regimens with induction of remission of poor prognosis acute myeloid leukemia (AML). Challenges remain in the expansion of these NK cells once infused and in their education to recognize tumor targets. A principal mechanism of tumor recognition is through KIR mismatch in cells lacking self MHC I molecules. Activating KIRs exist, though their ligands are unknown at this time. Impacting NK cell expansion and education in vivo has been challenging, and thus far clinical applications of NK cells have shown promise in helping to maintain remission in humans, though this remission has not been maintained. Future efforts to utilize NK cells clinically are focusing on developing more consistency in successful expansion of NK cell and educating them to recognize their tumor targets. Additional efforts to utilize novel antibody-based therapy to engage NK cells to their tumor targets are also in development.